The paradise problem - Lauren, Christina (Gallery Books, 2024)
"Anna Green thought she was marrying Liam "West" Weston for access to subsidized family housing while at UCLA. She also thought she'd signed divorce papers when the graduation caps were tossed, and they both went on their merry ways. Three years later, Anna is a starving artist living paycheck to paycheck while West is a Stanford professor. He may be one of four heirs to the Weston Foods conglomerate, but he has little interest in working for the heartless corporation his family built from the ground up. He is interested, however, in his one-hundred-million-dollar inheritance. There's just one catch. Due to an antiquated clause in his grandfather's will, Liam won't see a penny until he's been happily married for five years. Just when Liam thinks he's in the home stretch, pressure mounts from his family to see this mysterious spouse, and he has no choice but to turn to the one person he's afraid to introduce to his one-percenter parents - his unpolished, not-so-ex-wife. But in the presence of his family, Liam's fears quickly shift from whether the feisty, foul-mouthed, paint-splattered Anna can play the part to whether the toxic world of wealth will corrupt someone as pure of heart as his surprisingly grounded and loyal wife. Liam will have to ask himself if the price tag on his flimsy cover story is worth losing true love that sprouted from a lie"--